A numerical analysis of the impact of gas pressure and dielectric material on the generation of body force in an air gas plasma actuator - Hajikhani, Sajad; Mehrabifard, Ramin; Ahmadi, Hamed Soltani (Radiation Physics and Engineering, 2024)
Plasma technology has undeniably revolutionized industrial processes in recent decades. Atmospheric pressure plasma (APP) has emerged as a prominent and widely applicable tool in various scientific disciplines. Notably, plasma-assisted flow control has become a subject of intense interest, particularly applying surface dielectric barrier discharge (SDBD) plasma actuators for aerodynamic flow control. In this study, a two-dimensional model of the SDBD plasma actuator is developed using the COMSOL Multiphysics program, incorporating air gas discharge reactions with N2/O2/Ar gases in specific ratios (0.78, 0.21, 0.01). The investigation focuses on the impact of dielectric materials (mica, silica glass, quartz, and polytetrafluoroethylene (PTFE)) on plasma characteristics and body force within the plasma actuator under constant input parameters. Moreover, the study explores how variable pressure (760, 660, and 560 torr) in different applications influences plasma properties, ultimately affecting the magnitude of the body force in the plasma actuator. These findings contribute to optimizing plasma technology for flow control applications and enhance industrial efficiency and performance.